Sustainable consumption facts and trends from a business perspective - World Business Council for Sustainable Development ([Geneva, Switzerland] World Business Council for Sustainable Development, 2008)
This document takes stock of recent developments and trends in global consumption patterns. It presents an overview of documented facts and trends on the relationship between business activities, consumer behavior, and environmental and social challenges.
The primary purpose of this paper is to stimulate further discussion among businesses and to be used in dialogue with stakeholders. We have used existing data from a variety of sources, including intergovernmental organizations, non-governmental organizations (NGOs), governments, academics, consumer groups and businesses, including our own members. In all cases, we have sought to use the best data available.
Global drivers of consumption -- Global consumption patterns & impacts -- The role of the consumer -- The role of business -- The challenge ahead & options for change.
Title from cover.
Includes bibliographical references (p. 37-38)
Keywords: Sustainable development; Economic development -- Environmental aspects; Social responsibility of business